Determination of Interesting Toxicological Elements in PM2.5 by Neutron and Photon Activation Analysis - Pasquale Avino; Geraldo Capannesi; Francesco Lopez; Alberto Rosada (The Scientific World Journal)
Human activities introduce compounds increasing levels of many dangerous species for environment and population. In this way, trace elements in airborne particulate have a preeminent position due to toxic element presence affecting the biological systems. The main problem is the analytical determination of such species at ultratrace levels: a very specific methodology is necessary with regard to the accuracy and precision and contamination problems. Instrumental Neutron Activation Analysis and Instrumental Photon Activation Analysis assure these requirements. A retrospective element analysis in airborne particulate collected in the last 4 decades has been carried out for studying their trend. The samples were collected in urban location in order to determine only effects due to global aerosol circulation; semiannual samples have been used to characterize the summer/winter behavior of natural and artificial origin. The levels of natural origin element are higher than those in other countries owing to geological and meteorological factors peculiar to Central Italy. The levels of artificial elements are sometimes less than those in other countries, suggesting a less polluted general situation for Central Italy. However, for a few elements (e.g., Pb) the levels measured are only slight lower than those proposed as air ambient standard.